MODEL PENDIDIKAN POLITIK PARTAI GERINDRA KOTA TANGERANG SELATAN PADA PEMILU 2019: Analisis Pendidikan Politik Dalam Meningkatkan Dan Mempertahankan Keterwakilan Kader Di DPRD Kota Tangerang Selatan - Nourma Luthfiyyah Malawat (2023)
Political parties provide political education to cadres so that they can produce superior and responsible cadres in carrying out their duties as good citizens. This research will examine the political education model by the Gerindra Party DPC Tangsel Citywhichhas been given to cadres in increasing and maintaining the representation of cadres in the DPRD of Tangsel City. This study uses a qualitative approach using educational theory by Kartono. The research results obtained show the influence of the political education model of the Gerindra Party DPC Tangsel City in an effort to maintain and increaseparty representation in the Tangsel City DPRD in the 2019 election which has proven successful with program implementation during the campaign as a step to get closer to the community. Gerindra Party DPC Tangsel City managed to win votes whichhavecontinued to increase since the 2014 legislative elections, namely 79,844 votes (12.82%) and in 2019 101,289 votes (13.50%). Then, the elected Gerindra Party Fraction DPRD Members of South Tangerang City have actively participated in building a more advanced South Tangerang. One of them is by voicing reforms for the City of Tangsel whichareaddressed directly to the City Government of Tangsel.